POLITIK HUKUM DALAM BIDANG HUKUM KELUARGA ISLAM DI INDONESIA - Fitra Mulyawan; Kiki Yulinda; Dora Tiara (Ensiklopedia Social Review, 2021)
In Indonesia, religion and state are two different entities, and each has its own autonomy, where there is an area that is completely “belonging to” religion, the state cannot enter it and there is also an area that is fully the competence of the state, so religion is not can participate in it. So that the formation of laws will reflect the configuration of power and political interests. In the actualization of political power and interests, sometimes there is a clash between the interests of fragmatism and those that are permanent and in favor of the benefit of mankind. This means that the interests of ideological values that live and develop in society can be configured with the interests of political power fragmatism. Therefore, first, the legislative program for several aspects of the modernization of Islamic family law politics in Indonesia, namely starting with the history of legislation on marriage in Indonesia, one of which is the Dutch East Indies Government circulating the Draft Ordinance on Registered Marriage, which includes the principle of monogamy and the prohibition of imposing divorce out of court. Then from the point of view of the meaning of the ideal law, the presence of KHI is a series of historical national laws that can reveal the various meanings of the life of the Indonesian Muslim community. Second, before the birth of Law no. 1 of 1974 in Indonesia various marriage laws apply for various groups of citizens and various regions. in the Indieche Staats Regeling (ISR), namely the Indian constitutional regulations. After independence, the Indonesian government has established a number of Islamic marriage regulations. Among them are Law Number 22 Year 1946 concerning Registration of Marriage, Divorce and Reconciliation.